CRITICAL EPISTEMOLOGY OF CRONE AND COOK’S THOUGHT IN “HAGARISM: THE MAKING OF THE ISLAMIC WORLD” - M. Rizqi Aulia (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This research analyzes the ideas of Patricia Crone and Michael Cook as presented in their work, “Hagarism: The Making of the Islamic World,” published in 1977. This seminal text introduces a revisionist approach that challenges traditional narratives surrounding the origins of Islam through the utilization of non-Muslim sources and critical methodologies. The study explores the central arguments posited by Crone and Cook regarding the formation of the Islamic world, with a particular emphasis on the complex context of imperial civilization, including the influences of Zoroastrianism, Jewish traditions, Nestorian Christianity, and Roman law. Employing a historical-critical analytical method, this paper also examines the methodological and epistemological implications of their approach to contemporary Islamic historiography. The findings of this study indicate that, while Hagarism provides a significant new perspective, the reliance of Crone and Cook on non-Muslim sources may lead to misunderstandings regarding Islamic history. Furthermore, their work fosters further discourse on acculturation and historical change within the context of Islam's formation, while simultaneously inciting critiques concerning the objectivity and reliability of sources in historical studies.